RUSSIAN-KYRGYZ ECONOMIC COOPERATION: PROBLEMS AND SOLUTIONS (1999-2013) - A. Ormonova (Publishing House of the State University of Management, 2017)
This article presents a brief analysis of economic problems between the Russian Federation and the Kyrgyz Republic from 1999 to 2013, and suggested ways to solve them. The article considers topical issues of export-import, electric power, gas, agrarian, investment development of relations between partner countries.